Phenotypes in Children With SYNGAP1 Encephalopathy in China - Zhang, Huiting; Yang, Liu; Duan, Jing; Zeng, Qi; Chen, Li; Fang, Yu; Hu, Junjie; Cao, Dezhi; Liao, Jianxiang (Frontiers in Neuroscience, 2021)
Abstract Objective: We aimed to explore the associated clinical phenotype and the natural history of patients with SYNGAP1 gene variations during early childhood and to identify their genotype-phenotype correlations. Methods: A cohort of 13 patients with epilepsy and developmental disorder due to SYNGAP1 mutations, including seven patients from Shenzhen Children’s Hospital between September 2014 and January 2020 and six patients from previously published studies. Their clinical data were studied and analyzed. were analyzed. Results: A total of 13 children with SYNGAP1 gene variants (eight boys and five girls) were identified. The age of disease onset was in infancy. Mutations were located between exons 8 and 15; most were frameshift or truncated mutations. Four mutation sites (c.924G>A, c.1532.2_1532del, c.1747_1755dup, c.1735_1738del) had not been reported before. All patients had global developmental delay within the first year of life, and intellectual impairment became gradually apparent. Some of them developed behavioral problems. The developmental delay occurred before the onset of seizures. All seven patients in our cohort presented with epilepsy; myoclonic seizures, absence seizures and epileptic spasms were the most common seizure types. Abnormal electroencephalograms were identified from five patients before the onset of their seizures. All patients suffered drug-resistance seizures. However, comorbidities such as behavioral problems were less frequently observed. Conclusion: The most common age of disease onset in SYNGAP1 mutations is in infancy, while neurodevelopmental delay and epilepsy are the major phenotypes. They have a higher percentage of drug-resistant epilepsy and epileptic spasms than those in previous reports. We should give attention to the patients with abnormal EEGs without seizures and think about the suitable time of the anti-seizure medications for them. We have not found the genotype-phenotype correlation.